Evaluations of the uptake and impact of the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) Statement and extensions: a scoping review - Page, Matthew J; Moher, David (Université d'Ottawa | University of Ottawa, 2017)
Abstract Background The PRISMA Statement is a reporting guideline designed to improve transparency of systematic reviews (SRs) and meta-analyses. Seven extensions to the PRISMA Statement have been published to address the reporting of different types or aspects of SRs, and another eight are in development. We performed a scoping review to map the research that has been conducted to evaluate the uptake and impact of the PRISMA Statement and extensions. We also synthesised studies evaluating how well SRs published after the PRISMA Statement was disseminated adhere to its recommendations. Methods We searched for meta-research studies indexed in MEDLINE® from inception to 31 July 2017, which investigated some component of the PRISMA Statement or extensions (e.g. SR adherence to PRISMA, journal endorsement of PRISMA). One author screened all records and classified the types of evidence available in the studies. We pooled data on SR adherence to individual PRISMA items across all SRs in the included studies and across SRs published after 2009 (the year PRISMA was disseminated). Results We included 100 meta-research studies. The most common type of evidence available was data on SR adherence to the PRISMA Statement, which has been evaluated in 57 studies that have assessed 6487 SRs. The pooled results of these studies suggest that reporting of many items in the PRISMA Statement is suboptimal, even in the 2382 SRs published after 2009 (where nine items were adhered to by fewer than 67% of SRs). Few meta-research studies have evaluated the adherence of SRs to the PRISMA extensions or strategies to increase adherence to the PRISMA Statement and extensions. Conclusions Many studies have evaluated how well SRs adhere to the PRISMA Statement, and the pooled result of these suggest that reporting of many items is suboptimal. An update of the PRISMA Statement, along with a toolkit of strategies to help journals endorse and implement the updated guideline, may improve the transparency of SRs.